Dynamics and landscape of academic discourse on environmental attitudes and behaviors since the 1970s - Telesiene, Audrone; Hadler, Markus (Frontiers in Sociology, 2023)
Introduction This study addresses the lack of systematic review and analysis of the academic discourse on environmental attitudes and behaviors. Despite the wealth of knowledge published in academic journals, there is a need to understand the order and content of this discourse, including the employed theoretical approaches and empirical evidence. Methods A combination of systematic literature review and quantitative content analysis methods was employed. Articles for analysis were identified through Web of Science and SCOPUS, followed by a detailed analysis of 200 papers from the journal Environment and Behavior. The study aimed to explore the historical stages, theoretical diversity, and the empirical evidence brought forward in the academic discourse on environmental attitudes and behaviors. Results The findings reveal distinct historical stages within the academic field of environmental attitudes and behaviors. There is a notable growth in theoretical diversity and intensity of the discourse, particularly after 2000. The dominance of socio-psychological explanatory models is evident. Furthermore, the empirical evidence base is geographically limited, mostly coming from the US. Discussion The study discusses the limitations of the academic discourse on environmental attitudes and behaviors and provides guidelines for future research. It emphasizes the need to address the identified shortcomings, such as expanding theoretical perspectives and increasing the geographical diversity of empirical evidence. The study's findings contribute to understanding the development and characteristics of the academic field, while also identifying avenues for further exploration.